6
Step-by-step explanation
Step 1
Let x represents the score of the first day
total score=0
score of the second day=-6
then
Total score= score of the first day+score of the second day
replacing
![\begin{gathered} 0=x+(-6) \\ 0=x-6\text{ Equation} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4vh14a01muxnx3in9ltaxr4ccvmp9uh56m.png)
Step 2
solve the equation
![\begin{gathered} 0=x-6 \\ \text{add 6 in both sides} \\ 0+6=x-6+6 \\ 6=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/e1fpqosaa60rkhcjici2xy85497x08553z.png)
Hence, the score of the first day is 6
I hope this helps you